Control of Aflatoxin Production of Aspergillus flavus and Aspergillus parasiticus Using RNA Silencing Technology by Targeting aflD (nor-1) Gene. - Abdel-Hadi, Ahmed; Caley, D. P.; Carter, D. R.; Magan, Naresh (MDPI, 2011)
Aspergillus ﬂavus and Aspergillus parasiticus are important pathogens of cotton, corn, peanuts and other oil-seed crops, producing toxins both in the field and during storage. We have designed three siRNA sequences (Nor-Ia, Nor-Ib, Nor-Ic) to target the mRNA sequence of the aflD gene to examine the potential for using RNA silencing technology to control aflatoxin production. Thus, the effect of siRNAs targeting of two key genes in the aflatoxin biosynthetic pathway, aflD (structural) and aflR (regulatory gene) and on aflatoxin B(1 )(AFB(1)), and aflatoxin G(1) (AFG(1)) production was examined. The study showed that Nor-Ib gave a significant decrease in aflD mRNA, aflR mRNA abundance, and AFB(1) production (98, 97 and 97% when compared to the controls) in A. flavus NRRL3357, respectively. Reduction in aflD and aflR mRNA abundance and AFB(1 )production increased with concentration of siRNA tested. There was a significant inhibition in aflD and AFB(1) production by A. flavus EGP9 and AFG(1 )production by A. parasiticus NRRL 13005. However, there was no significant decrease in AFG(1) production by A. parasiticus SSWT 2999. Changes in AFB(1) production in relation to mRNA levels of aflD showed a good correlation (R = 0.88; P = 0.00001); changes in aflR mRNA level in relation to mRNA level of aflD also showed good correlation (R = 0.82; P = 0.0001). The correlations between changes in aflR and aflD gene expression suggests a strong relationship between these structural and regulatory genes, and that aflD could be used as a target gene to develop efficient means for aflatoxin control using RNA silencing technolog